BIOLOGI REPRODUKSI IKAN JUARO (Pangasius polyuranodon) DI DAERAH ALIRAN SUNGAI MUSI, SUMATRA SELATAN - Yunizar Ernawati; Eko Prianto; A. Ma'suf (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Study on biology reproduction was expected to give basic information for management, such as for aquaculture, capture fisheries and conservation of P. polyuranodon in Musi river. Sampling were conducted on June 2006, August 2006, January 2007, and July 2007 in Musi river by using gillnet. Data analysis included length-weight relationship, sex ratio, condition factor, gonad maturity stage, Gonadosomatic Index (GSI), fecundity, and spawning type. Total number of collected P. polyuranodon was 51, consisted of 23 male and 28 female. Total length of fish was ranged in 85–511 mm. Length-weight relationship of male and female was W = 0.00002L2.8062 and W = 0.0002L2.8215 respectively. The result from t-test analysis showed that both of sexes have allometric negative growth. Sex ratio thoroughly was balance (1:1). Mean of factor condition relatively increased by the increasing of gonad maturity stage. At that time P. polyuranodon was entering spawning time. June and August was predicted as the spawning time of this species. Gonadosomatic index of female was much higher than the male. Fecundity of female was ranged between 616 and 7,059. Based on distribution of egg diameter, this species was total spawner.